RETROSPECTIVE STUDY ON HIGHLY PATHOGENICAVIAN INFLUENZA H5N1 OUTBREAKS DURING 2006 -2008 IN ICT, PAKSITAN - Z. Fatima; M. A. Khan; K. Naeem; M. U. D. Ahmad; K. Muhammad; M. H. Mushtaq; Z. Anwar; A. Khan; M. L. Sohail (Journal of Animal and Plant Sciences, 2017)
Here we present the findings of the retrospective data collected from April 2006 to June 2008 regarding highly pathogenic avian influenza virus H5N1outbreaks in commercial poultry farms. The results showed that most of these outbreaks affected 45 weeks old layers and breeder farms. The cumulative morbidity was 57-95% and mortality was 5-43%.The highest culling percentage was recorded in layers (95.29%). Mortality, morbidity, case fatality was significantly (P<0.05) higher in layers than breeders and broilers. While culling rate was higher in broilers. Seasonal impact was recorded on incidence of outbreaks in commercial poultry farms in the study area i.e. most of the outbreaks occurred in the months of April, May and June in the year 2006, 2007 and 2008.It was concluded that the enormous losses due to 2006 -2008 outbreaks were due to high rate of mortality and morbidity mostly in adult birds especially in layer and breeder farms when they were in or near to egg laying stage of life. To combat and prevent future endemics, a regular sero-surveillance programs should be conducted on regular basis to identify HPAI viral strains in Pakistan.
Keywords: HPAI; ICT; Pakistan; surveillance; outbreaks; Poultry